Pembuatan Sistem Informasi Akuntansi Pada Toko NKL Surabaya - Fuhji Ericko; Leo Willyanto Santoso; Alexander Setiawan (Jurnal Infra, 2018)
NKL Store is a company that works in the distribution of textile and gentlemen’s tailor. Unfortunately it doesn’t have a good financial and transaction report. Based on this background, a structured Accounting Information System that made by programming language such as PHP (Hypertext Preprocessor), HTML (Hyper Text Markup Language), and MYSQL as databases. The output of this application is master report, structured and computerized sale and purchase report complete with stock card by average method, then lastly financial report of profit and loss and balance sheet of Toko NKL.